Incidencia de parásitos gastrointestinales en cerdos de crianza a nivel familiar, en la parroquia la Unión, cantón Babahoyo - López Delgado, Fabrizio Miguel (2024)
In the present experimental investigation, it was carried out with the purpose of detecting the prevalence of gastrointestinal parasites in the different families dedicated to pig production within this area of the country such as the La Unión parish, in the Babahoyo canton of the province of Los Ríos. , taking 100 fecal samples where analysis was carried out under the microscope, using the flotation technique, establishing evaluation parameters in pigs for parasitic detection by identifying parasites that harbor the gastrointestinal area of pig individuals. , with prevalence of factors of race, sex, age and origin. Taking into account the sanitary management that each of the families that are dedicated to raising pigs has. Once this research was developed, the following results were obtained with a total of 100 individuals negative for the presence of gastrointestinal parasites, resulting in 100 pigs sampled in their entirety and transparency, the data stabled using Chi-Square yielded a non-significant result.